Hubungan Dukungan Keluarga dan Discharge Planning Terhadap Kualitas Hidup Pasien Ulkus Diabetikum - Husna Fadhlia; Yunisman Roni; Aminatul Fitri (Universitas Karya Husada Semarang, 2025)
Introduction: Diabetic ulcers can affect the quality of life of sufferers. Support from family and health workers in the form of discharge planning is needed to help improve the quality of life of diabetic ulcer patients. Onjective: This study aims to determine the relationship between family support and discharge planning on the quality of life of diabetic ulcer patients. Method: This study used a correlational method with a cross-sectional approach. The research sample was 50 respondents based on inclusion and exclusion criteria using accidental sampling. The instruments used were the WHOQOL-Bref questionnaire, family support questionnaire, and discharge planning questionnaire. The analysis used was bivariate analysis with Kendall's tau-b correlation test. Results: Of the 50 respondents, there were 37 respondents (74%) with moderate quality of life, 28 respondents (56%) with high family support, and 40 respondents (80%) with good discharge planning. The results of statistical tests show that there is a significant relationship between family support and the quality of life of ulcer patients with a p value of 0.000 <α (0.05), and there is a significant relationship between discharge planning and the quality of life of ulcer patients with a p value of 0.006 <α (0.05). Conclusion: There is a relationship between family support and the quality of life of diabetic ulcer patients and there is a relationship between discharge planning and the quality of life of diabetic ulcer patients. Family support is more significant in influencing the quality of life of diabetic ulcer patients.